Obtenção e condutividade elétrica de vitrocerâmica Li1+xAlxTi2-x(PO4)3 com diferentes microestruturas - Semanate, José Luis Narváez (Universidade Federal de São Carlos, 2009)
Technological advances in portable devices imply not only the development of devices but also the need to enhance their power sources. For instance, cellular phones with high technology incorporating Bluetooth, Infrared, Digital Camera, Games, GPS, Internet Browsing, etc., need high performance rechargeable batteries. Lithium ion-conducting glass-ceramics with NASICONtype structure, based on the Li1+xMxM'2-x(PO4)3 system, where M = Al, Cr, Fe, Ga and M' = Ge, Ti, Hf, are considered good candidates as solid electrolytes in lithium ion batteries due to their chemical stability, easy fabrication and high ionic conductivity. In this work, the Li1+xAlxTi2-x(PO4)3 glass composition was synthesized by the traditional method known as Splat Cooling. Glass-ceramics with the same composition as the precursor glass but with different microstructures were obtained by controlled crystallization, using single and double heat treatments. The parent glass was characterized by chemical and thermal analysis and the latter enabled tailoring of the crystallization heat treatments. X-ray diffraction (XRD) results indicated that the resulting glassceramics exhibit the desired NASICON-type structure as primary phase, as well as the segregation of insulating phases, i.e., AlPO4 and/or TiO2, which do not affect the electrical properties. An examination of the microstructure by scanning electron microscopy (SEM) and measurements of electrical conductivity by impedance spectroscopy (IS), combined with the XRD analysis, indicated that the electrical conductivity of single heat-treated samples increases with the heat treatment temperature and hence with the increase in crystallinity. Samples synthesized by double heat treatment showed increasing electrical conductivity with decreasing nucleation treatment time and consequently with increasing average grain size.
Synthesis and electrical conductivity of Li1+xAlxTi2-x(PO4)3 glass-ceramic with different microstructures
Keywords: Materiais; Cristalização; Nucleação; Espectroscopia de impedância; Tamanho de grão; Cristalinidade; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA